Physico-Chemical, Organoleptic, and Antioxidant Properties of Black Soybean Flour (Glycine soja (L.) Merrit) Flakes with the Addition of Bangle (Zingiber purpureum Roxb.) - Kumalasari, Ika Dyah; Nurkhasanah, Nurkhasanah; Sepitriani, Sepitriani (Pharmaceutical Sciences and Research, 2024)
Flakes are products that are generally made from cereals. In this study, we are interested to use black soybean (Glycine soja (L) Merrit) and bangle (Zingiber purpureum Roxb.) as flakes ingredients. Black soybeans have high antioxidant components, while bangle contains high antioxidant and fiber components, which enables it to capture free radicals. This study aimed to find the most favorable formula with good physical, chemical, and organoleptic characteristics, which also has the highest antioxidant activity. We used the Completely Randomized Design (CRD) method and the variation of formulation used was the ratio of black soybean flour to bangle as follows: T1 (100%:0%), T2 (95%:5%), T3 (90%:10%), T4 (85%:15%), and T5 (80%:20%). The parameters analyzed included physical properties (color, texture, and water absorption), chemical properties (moisture content, ash content, fat content, protein content, carbohydrate content, crude fiber content, and antioxidant activity, as well as total plate count), and organoleptic properties (color, texture, taste, aroma, and overall acceptance). The research data were analyzed using One-Way Analysis of Variance (ANOVA) at a significance level of 5% and Duncan’s multiple range test. The results showed that the best formula for color and texture is T5 L* 54.57, a*-4.22, color b*31.42, hardness 0.74N, and water absorption 30.01%. The best treatment for chemical properties is T5 (moisture: 4.26%, ash: 3.68%, fat: 18.16%, protein: 16.92%, carbohydrate: 56.98%). All formulations meet the total plate count of <2,500. The highest antioxidant activity was in the T5 formulation (49.59 %). The results of the organoleptic properties showed that the most favorable overall organoleptic reception was T1. Flakes based on black soybean flour with the addition of bangle in formulation T5 (80% black soybean flour: 20% bangle) have the potential to be a functional food high in fiber and antioxidants.